Numerical simulation of temperature fluctuation reduction by a vortex breaker in an elbow pipe with thermal stratification. (January 2015) - Lu, T.; Han, W.W.; Zhai, H.
Highlights: Thermal stratification can cause thermal fatigue in an elbow pipe. Temperature fluctuations were modeled by large-eddy simulation. Temperature fluctuations can be reduced by fixing a vortex breaker. Abstract: Thermal fluctuations in an elbow pipe with thermal stratification can readily lead to thermal fatigue in a nuclear power plant, and hence have attracted considerable attention in nuclear engineering and technology. This work describes a mathematical model for the study of the mechanism of heat transfer in an elbow pipe with thermal stratification. The temperature fluctuations of the fluid are modeled by means of large eddy simulations on the FLUENT platform. The numerical results show that temperature fluctuations in the elbow pipe can be reduced by fixing a vortex breaker in the upper straight pipe.